Hubungan Antara Dukungan Sosial dan Hardiness dengan Kesejahteraan Psikologis Pada Wanita Bekerja - Dharmastuty, Galuh; , Dr. Nanik Prihartanti,M.Si (2016)
Psychological well-being is a condition experienced by an individual either being happy, unhappy, satisfied, or pleased felt by himself/herself regarding problem and satisfaction in his/her life, therefore, it can help the individual in controlling the life and growing independently. Psychological well-being emerged due to the social support and a strong personality (hardiness). The purpose of this research was to know the correlation between social support and hardiness and psychological well-being in career women. The subjects of the research were 60 career women. The methods of collection data used the scale of psychological well-being, the scale of social support, and the scale of hardiness. The technique of sampling used quota sampling. The method of data analysis used the regression analysis. The results of the research revealed that (R) 0.583; p = 0.000 (p < 0.01) that meant that there was a positively significant correlation between social support and hardiness and psychological well-being, in which the higher the social support and the hardiness, the higher the psychological well-being was. On the contrary, the lower the social support and the hardiness, the lower the psychological well-being of someone was. The effective contribution of social support and hardiness was as much as 34% in this research.